Arkitekturang Filipino spaces & places in history (Pambansang Komisyon para sa Kultura at mga Sining, 2002)
Presents and expresses an alternative approach to understanding architecture. Contrary to traditional notion of architecture of resulting object or product, this CDROM highlights the concept of architecture as a process. Which takes root from its interactions with the society and natural environment. Through this perspective, architecture is freed from a frozen construct and object-oriented definition.--container.